Validation of a Model Estimating the Budget Impact of Video Capsule Endoscopy for Surveillance of Crohn’s Disease in an Italian Center - Rhodri Saunders; Carlo Calabrese; Dania Gelli; Jason Davis; Rafael Torrejon Torres (Journal of Health Economics and Outcomes Research)
**Background:** Crohn's disease is a chronic ailment affecting the gastrointestinal tract. Mucosal healing, a marker of reduced disease activity, is currently assessed in the colonic sections using ileocolonoscopy and magnetic resonance enteroscopy. Video capsule endoscopy (VCE) offers visualization of the entire GI mucosae.